Penerapan Pijat Oksitosin Oleh Suami Terhadap Produksi Asi Pada Ibu Nifas Di Desa Ngrukuh Kabupaten Klaten - Nabila Luthfiah Sungkar; Norman Wijaya Gati (STIKes Ibnu Sina Ajibarang, 2023)
Background: A survey in Indonesia reported that 38% of mothers stopped giving breast milk due to a lack of milk production.Oxytocin massage is one of the solutions to overcome the irregularity of milk production. Oxytocin massage is massage along the spine (vertebrae) to the fifth-sixth costae and is an attempt to stimulate the hormones prolactin and oxytocin after childbirth. Oxytocin massage is done to stimulate the oxytocin reflex (milk ejection) or the let down reflex (flow reflex). Purpose: the purpose of this study was to determine the effect of oxytocin massage by husbands on increasing milk production in postpartum mothers in Ngrukuh Village, Klaten Regency. Methods: This research was conducted in June 2023. This type of research uses a case study research design. Samples were 2 (two) postpartum mothers. Measuring the adequacy of breast milk in the oxytocin massage procedure with the length of time the intervention was carried out for ± 15 minutes and the frequency of giving therapy 1-2x a day for 14 days. Data analysis was carried out by looking at the breastfeeding adequacy observation sheet. Results: The results of the study showed that the level of milk production before the oxytocin massage was carried out, namely that milk production did not include signs of sufficient milk supply and after being given oxytocin massage, the level of milk production included signs of sufficient milk supply. Conclusion: There is a significant influence between the level of milk production experienced by postpartum mothers before and after being given oxytocin massage.